(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Nanotechnology is very useful in manipulating the matter that there is scope of improvement in technologies in order to secure the environment. With the help of nanotechnology, we can get an advanced technology which is capable of providing the dimensions of high accurate. Currently, the usage of nano technology can be seen in the commercial market in the form of nano devices and nano materials which are playing a revolutionary part in the implications of safety, health and advancement in technology. The applications of nano technology can be seen in almost every field of life resulting in making the daily life tasks so easier for the current and future generation. The purpose of this paper is to explore various uses of nanotechnology in metrology, Electronics, Optoelectronics, Nanomedicines, Bionanotechnology and other fields.